Toward value creation in local authorities: the role of information and communication technologies - Amrani, Nouha; Sadik, Mohammed; Chnigri, Youssra; Hemmi, Mohamed; Slimani, Hamid; Skačkauskienė, Ilona (Business, Management and Economics Engineering, 2022)
Purpose – The aim of this paper is to focus on the use of Information and Communication Technologies (ICT) by local authorities (LAs) in order to understand to which extent, they impact the value chain of local public services. The value creation in this article concerns not only economic effectiveness and efficiency but also the articulation and development of ICTs in the strategy of the LA, as well as the impact on citizen satisfaction.Research methodology – The methodology applied is quantitative, based on a questionnaire addressed to managers and officials in different Moroccan LAs (regions, provinces and prefectures, municipalities). SPSS 25 was used as a materiel to analyze the result of the linear regression.Findings – The results obtained confirm the importance of ICT in terms of optimization of expenses, the improvement of the quality of work by facilitating communications between services. In addition, the ICT are no longer centered on the managerial side, but contribute to the consecration of good governance principles, namely transparency and citizen participation.Research limitations – The present research excludes political leaders throughout data collection. Methodologically speaking, this means that the study can also take on the meaning of an exploratory study with qualitative method (interviews, case studies) in order to understand how these ICT, contribute to local public value creation.Practical implications – The research provides clues to LA managers about the importance of ICT and their contribution to value creation. The results obtained encourage decision makers to accept this change and to adopt the ICT approach in order to provide a higher quality of services.Originality/Value – The originality of this paper lies in the variables and the context in which they are studied. The existing literature interested in introducing ICTs in the public sector focus on the use of these tools to achieve economic performance. Furthermore, only a few research papers have been conducted on value creation in LA including the impact of ICT which justifies the originality and novelty of this paper.